DLG5 variants do not influence susceptibility to inflammatory bowel disease in the Scottish population - Noble, CL; Nimmo, ER; Drummond, H; Smith, L; Arnott, IDR; Satsangi, J (BMJ Publishing Group, 2015)
Introduction: Recent data have suggested that specific haplotypic variants of the DLG5 gene on chromosome 10q23 may be associated with susceptibility to inflammatory bowel disease (IBD) in Germany. Haplotype D, notably characterised by the presence of a G→A substitution at nucleotide 113, was associated with susceptibility to Crohn’s disease (CD) whereas an extended haplotype A conferred protection.